2022
DOI: 10.1182/bloodadvances.2021005564
|View full text |Cite
|
Sign up to set email alerts
|

Tisagenlecleucel outcomes in relapsed/refractory extramedullary ALL: a Pediatric Real World CAR Consortium Report

Abstract: Chimeric antigen receptor (CAR) T-cells have transformed the therapeutic options for relapsed/refractory (R/R) B-cell ALL. Data for CAR therapy in extramedullary (EM) involvement is limited. Retrospective data was abstracted from the Pediatric Real World CAR Consortium (PRWCC) of 184 infused patients from 15 US institutions. Response (CR) rate, overall survival (OS), relapse-free survival (RFS), and duration of B-cell aplasia (BCA) in patients referred for tisagenlecleucel with EM disease (both CNS3 and non-CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…14 The PRWCC previously published outcomes using tisagenlecleucel for the treatment of EM disease and described that the presence of baseline EM disease versus BM-only disease was not a risk factor for nonresponse or relapse. 16 Here, we identify that the number of preinfusion lines of therapy is associated with increased likelihood of relapse, possibly explained by more recalcitrant tumor biology, and compromised T-cell fitness or cumulative toxicity. Clinical studies evaluating CD19-CAR in the upfront MRD+ refractory setting are ongoing (ClinicalTrials.gov identifier: NCT03876769).…”
Section: Discussionmentioning
confidence: 92%
“…14 The PRWCC previously published outcomes using tisagenlecleucel for the treatment of EM disease and described that the presence of baseline EM disease versus BM-only disease was not a risk factor for nonresponse or relapse. 16 Here, we identify that the number of preinfusion lines of therapy is associated with increased likelihood of relapse, possibly explained by more recalcitrant tumor biology, and compromised T-cell fitness or cumulative toxicity. Clinical studies evaluating CD19-CAR in the upfront MRD+ refractory setting are ongoing (ClinicalTrials.gov identifier: NCT03876769).…”
Section: Discussionmentioning
confidence: 92%
“…This study demonstrated that CNS involvement was also not associated with impaired survival. 21 Most recently, several studies have addressed the question of the optimal bridging to CAR-T cell therapy. 22,23 The question of whether previous CD19-directed immunotherapy with blinatumomab might contribute to treatment failure has gained particular importance.…”
Section: Discussionmentioning
confidence: 99%
“…Grade ≥ 3 neutropenia is observed in <40% of patients and the cumulative incidence of neutrophil recovery at 28 days was 75%. HGG was pronounced in roughly half of the cohorts, while irAEs, pre-therapy lymphopenia, and duration of low IgG were significantly associated with infection density [ 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ]. According to the FDA Adverse Event Reporting System for tisagenlecleucel in the post-marketing period for the pediatric population, infection was the second most frequent cause of death (11.3%) after disease progression [ 172 ].…”
Section: Chimeric Antigen Receptor T-cells (Car T-cells)mentioning
confidence: 99%